menu
QAmmunity.org
Login
Register
My account
Edit my Profile
Private messages
My favorites
Register
Ask a Question
Questions
Unanswered
Tags
Categories
Ask a Question
This is Josh’s solution for the equation x2-6x-7=0: x2-6x-7=0 x2-6x=7 x2-6x+9=7+9 (x-3)2=16 x=19 x-3=-16 x=-13 Is Josh’s solution correct? Explain
asked
Oct 28, 2019
48.2k
views
5
votes
This is Josh’s solution for the equation
x2-6x-7=0:
x2-6x-7=0
x2-6x=7
x2-6x+9=7+9
(x-3)2=16
x=19
x-3=-16
x=-13
Is Josh’s solution correct? Explain
Mathematics
high-school
Ashgromnies
asked
by
Ashgromnies
6.0k
points
answer
comment
share this
share
0 Comments
Please
log in
or
register
to add a comment.
Please
log in
or
register
to answer this question.
1
Answer
6
votes
No. After completing the square, Joshua should have taken the square root of the equation. As a result, he should have gotten:
x - 3 = 4 OR x - 3 = -4
And the result answer would have been x = 7 or x = -1
Sloneorzeszki
answered
Nov 1, 2019
by
Sloneorzeszki
6.3k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
Ask a Question
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.
6.5m
questions
8.7m
answers
Other Questions
What is the least common denominator of the four fractions 20 7/10 20 3/4 18 9/10 20 18/25
What is 0.12 expressed as a fraction in simplest form
What is the initial value and what does it represent? $4, the cost per item $4, the cost of the catalog $6, the cost per item $6, the cost of the catalog?
What is distributive property ?
What is the measure of xyz
Twitter
WhatsApp
Facebook
Reddit
LinkedIn
Email
Link Copied!
Copy
Search QAmmunity.org